Different expression pattern of flowering pathway genes contribute to male or female organ development during floral transition in the monoecious weed Ambrosia artemisiifolia L. (Asteraceae) - Kinga Klára Mátyás; Géza Hegedűs; János Taller; Eszter Farkas; Kincső Decsi; Barbara Kutasy; Nikoletta Kálmán; Erzsébet Nagy; Balázs Kolics; Eszter Virág (PeerJ, 2019)
The highly allergenic and invasive weed Ambrosia artemisiifolia L. is a monoecius plant with separated male and female flowers. The genetic regulation of floral morphogenesis is a less understood field in the reproduction biology of this species. Therefore the objective of this work was to investigate the genetic control of sex determination during floral organogenesis. To this end, we performed a genome-wide transcriptional profiling of vegetative and generative tissues during the plant development comparing wild-growing and in vitro cultivated plants. RNA-seq on Illumina NextSeq 500 platform with an integrative bioinformatics analysis indicated differences in 80 floral gene expressions depending on photoperiodic and endogenous initial signals. Sex specificity of genes was validated based on RT-qPCR experiments. We found 11 and 16 uniquely expressed genes in female and male transcriptomes that were responsible particularly to maintain fertility and against abiotic stress. High gene expression of homologous such as FD, FT, TFL1 and CAL, SOC1, AP1 were characteristic to male and female floral meristems during organogenesis. Homologues transcripts of LFY and FLC were not found in the investigated generative and vegetative tissues. The repression of AP1 by TFL1 homolog was demonstrated in male flowers resulting exclusive expression of AP2 and PI that controlled stamen and carpel formation in the generative phase. Alterations of male and female floral meristem differentiation were demonstrated under photoperiodic and hormonal condition changes by applying in vitro treatments.